MODELLING THE FINANCIAL FEASIBILITY OF RESIDENTIAL DEVELOPMENT - PUSPITA SARI (NIM 25005024), WULAN
The existing financial feasibility model of residential development only analyzed 2 of 3 residential development variables. Those variables are directly controlled variable and indirectly controlled variable. The uncertainty variable which also influenced the financial feasibility of residential development has not been analyzed into the model, so that the influence of uncertainty to the expected return and the investment risk has not yet been identified. Therefore, this research develop the financial feasibility model of residential development based on the existing model and analyzed the uncertainty variable into the model. In modelling the financial feasibility of residential development, monte carlo simulation with @Risk software is used to test the model based on case study scenarios. The model test result show the probability distribution of all possible developer’s expected returns which presented by financial feasibility criteria payback period, net present value (NPV) and internal rate of return (IRR). The model test result also show the investment risk which presented by coefficient of variation (CV) of the expected return. In this research, sensitivity analysis is used to identify the most influence uncertainty variable and the impact of that uncertainty variable to the expcted return.